How to cake it : a cakebook - Gampp, Yolanda (William Morrow, an imprint of HarperCollins Publishers, 2017)
From Yolanda Gampp, host of the massively popular, award-winning YouTube sensation How to Cake It comes an inspiring "cakebook" with irresistible new recipes and visual instructions for creating spectacular novelty cakes for all skill levels. On her entertaining YouTube Channel, How to Cake It, Yolanda Gampp creates mind-blowing cakes in every shape imaginable.